Shoulder Surfing Resistant Text Based Graphical Password Schemes Using Color - Ulya, Nurul Kholisatul; Nugroho, Lukito Edi; Adhipta, Dani (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Password is important information to access or enter a system. Alphanumeric is a text-based password system that is commonly used. Unfortunately, many users make a weak password that is easy to guess and vulnerable to various attacks such as brute-force, dictionary attack, guessing attack and others. To create a strong password is suggested to have a lot of variety and long, but it will be difficult to remember by the user. Graphical password is an alternative method that gives usability for the user. Based on psychological research, people are generally easy to remember or recognize an images, shapes and colors rather than text. This reinforces the researchers to develop this method. The main problem of graphical password isvulnerable to shoulder surfing. In this paper will be proposed scheme as graphical password text based that are resistant to shoulder surfing attacks using color.